Elevated Blood C-Reactive Protein Levels in Patients With Epilepsy: A Systematic Review and Meta-Analysis - Zhong, Rui; Chen, Qingling; Li, Mengmeng; Zhang, Xinyue; Lin, Weihong (Frontiers in Neurology, 2019)
Abstract Background In recent years, much more attention has been payed to the association between C-creative protein (CRP) levels and epilepsy risk. However, Studies concerning the CRP levels in epilepsy have also yielded conflicting results. Thus, the subjective of the present study is to systematically review the evidence and conduct a meta-analysis to investigate the role of CRP levels on risk of epilepsy. Methods A systematic search of PubMed, EMBASE and the Cochrane Library for eligible studies. Mean deviations (MDs) with 95% confidence intervals were used as a measure to assess the association between CRP and epilepsy. Results In total, 16 case-control studies were included in the present meta-analysis, which was comprised of 1918 individuals. Combined results indicated that epileptic patients had significant increased CRP levels in peripheral blood compared with healthy controls (SMD=0.43, 95%CI: 0.19-0.67). In addition, subgroup analyses on the basis of age group demonstrated that significant difference in blood CRP levels between epileptic patients and healthy controls was found in Adults (SMD=0.47, 95%CI: 0.21-0.73) rather than Children (SMD=0.26, 95%CI: -0.48-0.99). Conclusion The present meta-analysis shows that the CRP levels in peripheral blood were significantly increased in epileptic patients compared to healthy controls, indicating that CRP may be associated with the increased risk of epilepsy.